The Role And The Formal Requirements Of Powers Of Attorney At Trial Before The Administrative Court - Rahman, Andi Muhammad Ali (Universitas Islam Indonesia, 2020)
This study aims to determine the role of the special power of attorney in trials before the Administrative Court and to determine the formal requirements of making a special power of attorney in the administrative court. The benefits of this research are legal philosophyt and scientific development, especially in the field of procedural law, as well as to become an additional reference for those who are interested in researching this problem further. In addition, this research is expected to provide input for the community, students, and legal practitioners.This study uses normative legal approach or commonly called doctrinal research approach, including statutes and cases. The results of this study provide two conclusions: First, the role of special power of attorney in the trial at the Administrative Court is also applicable the principle of not having to use a power or legal aid. The use of mentoring or representation, authorization, legal aid is a right and not an obligation of a person. Such use is an obligation of the state when a citizen requires it but is unable to obtain it for themselves. Second, matters related to the formal requirements to become a special power of attorney in the Administrative Court have been spelled out in the Administrative Technical Guidelines and the Technical of Civil Service Arbitration Tribunal, Book II, edition 2009, the Supreme Court of the Republic of Indonesia.Keywords: constitution; power of attorney; administrative courtPeran Dan Syarat Formal Kuasa Hukum Dalam Persidangan Di Pengadilan Tata Usaha NegaraAbstrakPenelitian ini bertujuan untuk mengetahui the peranan dari kuasa hukum dalam persidangan di Pengadilan Tata Usaha Negara (PTUN) dan untuk mengetahui syarat formal kuasa hukum di PTUN. Manfaat penelitian ini adalah pengembangan filsafat hukum dan keilmuan khususnya di bidang hukum acara, serta menjadi tambahan referensi bagi yang tertarik untuk meneliti masalah ini lebih lanjut. Selain itu, penelitian ini diharapkan dapat memberikan masukan bagi masyarakat, mahasiswa, dan praktisi hukum. Penelitian ini menggunakan pendekatan hukum normatif atau biasa disebut dengan pendekatan penelitian doktrinal, termasuk undang-undang dan kasus. Hasil penelitian ini memberikan dua kesimpulan: Pertama, asas tidak harus menggunakan kuasa atau bantuan hukum berlaku untuk peran kuasa hukum dalam persidangan di PTUN. Penggunaan pendampingan atau perwakilan, otorisasi, bantuan hukum, atau kuasa hukum adalah hak dan bukan kewajiban seseorang. Penggunaan tersebut merupakan kewajiban negara jika warga negara membutuhkannya namun tidak dapat memperolehnya untuk diri mereka sendiri. Kedua, hal-hal yang berkaitan dengan persyaratan formal untuk menjadi kuasa hukum di PTUN telah diatur dalam Petunjuk Teknis Tata Usaha Negara dan Tata Usaha Arbitrase Kepegawaian, Buku II, edisi 2009, Mahkamah Agung Indonesia.Kata kunci: Konstitusi, Kuasa Hukum, Pengadilan Tata Usaha Negara